Lead-free halide double perovskites: Toward stable and sustainable optoelectronic devices. (October 2021) - Bibi, Asia; Lee, Ilgeum; Nah, Yoonseo; Allam, Omar; Kim, Heejun; Quan, Li Na; Tang, Jiang; Walsh, Aron; Jang, Seung Soon; Sargent, Edward H.; Kim, Dong Ha
Graphical abstract: Abstract: In recent years, metal halide perovskites (MHPs) have attracted attention as semiconductors that achieve desirable properties for optoelectronic devices. However, two challenges—instability and the regulated nature of Pb —remain to be addressed with commercial applications. The development of Pb-free halide double perovskite (HDP) materials has gained interest and attention as a result. This family offers potential in the field of optoelectronic devices through flexible material designs and compositional adjustments. We highlight recent progress and development in halide double perovskites and encompass the synthesis, optoelectronic properties, and engineering of the electronic structures of these materials along with their applications in optoelectronic devices. Computational and data-driven statistical methods can also be used to explore mechanisms and discover promising candidate double perovskites.